The end - LaRochelle, David; Egielski, Richard (New York : Arthur A. Levine Books, 2007)
When a princess makes some lemonade, she starts a chain of events involving a fire-breathing dragon, one hundred rabbits, a hungry giant, and a handsome knight.
3.2
K-3
Keywords: Characters and characteristics in literature -- Juvenile fiction; Fairy tales; Characters in literature -- Fiction; Fairy tales; Characters and characteristics in literature -- Fiction; Fairy tales